If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 = k + -2 Reorder the terms: 17 = -2 + k Solving 17 = -2 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 17 + -1k = -2 + k + -1k Combine like terms: k + -1k = 0 17 + -1k = -2 + 0 17 + -1k = -2 Add '-17' to each side of the equation. 17 + -17 + -1k = -2 + -17 Combine like terms: 17 + -17 = 0 0 + -1k = -2 + -17 -1k = -2 + -17 Combine like terms: -2 + -17 = -19 -1k = -19 Divide each side by '-1'. k = 19 Simplifying k = 19
| -12(x-(9))=3(x+16) | | -5(z+1)=-2z+10 | | 3Xsquared+5X=0 | | 1.4=n-2 | | -7x-(2.8)=6x-(13.2) | | 9s+9=30 | | 7x-(2.7)=-6x-(7.9) | | 8S-23=-14+5S | | 34-23= | | 180=3x+75 | | (x-2)2+(y+7)2=169 | | 7p-12=-36+4p | | 12k-3(k+5)=-8 | | 5y-y^2=11 | | y=5(2x-1)(x-4) | | 3x+8+3x+8+4x-4=180 | | 2x-14-8x=-26 | | 100=8y+4x | | 3(4s+9)=171 | | -4x+(5x-14)=136 | | 0.7+8q=4a-(-8q+3.3) | | 2x-y=450 | | 2.16=2x-1 | | 6a+2=5(a+2)-5a | | 3x-11=x+2 | | -6(x-(5))=3(x+1) | | -(1-b)=-4b+19 | | p=23+-75 | | -8(x-(4))=4(x-(13)) | | 4y-3-7b-5= | | 9-(x+4)=5x-37 | | 2+4(-3x-4)=18-4x |